Vitamin A supplementation coverage and its associated factors among children 6–59 months of age in Ethiopia: a systematic review and meta-analysis - Wondie, Wubet Tazeb; Zemariam, Alemu Birara; Gedefaw, Gezahagn Demsu; Lakew, Gebeyehu; Getachew, Eyob; Mengistie, Berihun Agegn; Shibabaw, Adamu Ambachew; Chereka, Alex Ayenew; Kitil, Gemeda Wakgari; Yirsaw, Amlaku Nigusie; Mekonnen, Gebrehiwot Berie (Frontiers in Public Health, 2025)
BackgroundVitamin A supplementation is a key strategy for preventing the consequences of vitamin A deficiency and childhood illnesses, notably in countries where vitamin A deficiency is a public health issue. However, studies in Ethiopia are inconsistent. Hence, this meta-analysis assessed coverage of vitamin A supplementation and associated factors among children aged 6–59 months in Ethiopia.MethodsA search of articles from databases (PubMed, Science Direct, African Index Medicus, and HINARI), and search engines (Google Scholar, Google, and Worldwide Science) was done. All observational studies that report vitamin A supplementation and/or associated factors among children were included. The Joana Brigs quality appraisal checklist was used. To estimate the pooled effect size a random effect model was used. Heterogeneity was evaluated using I2-test and Cochrane Q statistics. Subgroup and sensitivity analyses were conducted. Publication bias was assessed using Egger’s test and funnel plot.ResultsA total of 14 studies, involving 43,047 children aged 6–59 months, were included. The pooled vitamin A supplementation coverage was 54.88% (95% CI: 47.34–62.42). The lowest coverage 43.71%% (95% CI: 42.71–45.14) was among children 6–35 months. Four or more antenatal care (AOR: 1.79, 95%CI: 1.59–2.01), Postnatal care (AOR: 1.43, 95% CI: 1.24–1.66), delivery at health facilities (AOR: 1.14 95%CI: 1.02–1.28), media exposure (AOR: 1.19, 95% CI: 1.08–1.31), time to reach health facilities (AOR: 1.90, 95% CI: 1.11–3.24), information about VAS (AOR: 2.99, 95%CI: 1.72–5.20), maternal secondary education and above (AOR: 1.32, 95% CI: 1.07–1.64), and (AOR: 2.31, 95% CI: 1.31–4.09) respectively, and fathers education above secondary school (AOR:1.92, 95% CI: 1.13–3.26) were significant factors.ConclusionThe pooled vitamin A supplementation coverage is significantly below the WHO’s recommendation of 80%. Antenatal care, postnatal care, health facilities delivery, media exposure, time to reach health facilities, Information about VAS, maternal and paternal secondary education, and above increase VAS. Hence, the national nutritional program is better to increase awareness of the community about VAS, particularly targeting parents with low educational status and no antenatal and postnatal care through social media and community meetings. Additionally, the EPI program should strengthen outreach supplementations including door-to-door distribution to address older children and socio-economically disadvantaged populations.Systematic review registrationidentifier CRD42024576200.